COMPOSITION FOR TREATING INTESTINAL INFLAMMATORY DISEASE - ARNAUD FOUSSAT (2015)
PROBLEM TO BE SOLVED: To provide a therapeutic method of intestinal inflammatory disease, such as Crohn's disease, chronic ulcerative colitis, and intestinal inflammation associated with food allergy or intolerance.SOLUTION: A drug comprises at least one human Tr1 cell population against a food antigen from common human diet. The Human Tr1 cell population is human Tr1 clone population. The food antigen from common human diet is selected from the group comprising ovalbumin, casein, -lactoglobulin, soya protein, gliadin, peanuts, and fragments, variants and mixtures thereof. The drug or pharmaceutical composition administered to a subject in need thereof contains autologous human Tr1 cells against the subject's cells. The therapeutic method comprises the steps of obtaining Tr1 cells against a food antigen selected from common human diet from a subject's blood sample, expanding the obtained Tr1 cells, and intravenously reinjecting the Tr1 cells obtained from the subject. 【課題】クローン病、潰瘍性大腸炎、食物アレルギーまたは不耐性に関連する腸炎などの腸の炎症性疾患の治療方法の提供。【解決手段】ヒトの一般的食餌からの食物抗原に対する少なくとも１つのヒトＴｒ１細胞集団を含む薬剤。ヒトＴｒ１細胞集団はヒトＴｒ１クローン集団である。ヒトの一般的食餌からの食物抗原は、オボアルブミン、カゼイン、 −ラクトグロブリン、ダイズタンパク質、グリアジン、ピーナッツ、並びにそれらの断片、変異体及び混合物を含む群から選択される。治療を必要としている対象者に投与される薬剤又は薬学的組成物は、対象者の細胞に対して自家であるヒトＴｒ１細胞を含む。ヒトの一般的食餌から選択された食物抗原に対するＴｒ１細胞は、対象者の血液サンプルから入手されるステップと、得られたＴｒ１細胞を拡大するステップからなり、対象者において得られたＴｒ１細胞を静脈内経由で再注入するステップとを含む治療方法。【選択図】なし